2017
DOI: 10.3892/etm.2017.4274
|View full text |Cite
|
Sign up to set email alerts
|

Global methylation and promoter-specific methylation of the P16, SOCS-1, E-cadherin, P73 and SHP-1 genes and their expression in patients with multiple myeloma during active disease and remission

Abstract: Abstract. Tumor suppressor gene promoter CpG island methylation is a well-recognized mechanism in cancer pathogenesis, but its role in multiple myeloma (MM) is controversial. The present study investigated the methylation status and expression of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Genome-wide methylation arrays have been performed at several stages of MM disease, demonstrating the occurrence of DNA hypomethylation at early MM phases; importantly, the hypomethylated status was shown to further decline during MM progression [ 34 ]. Notably, promoter hypermethylation of several cancer-related genes (i.e., BNIP-3, p16, E-CAD, DAPK-1), was reported to correlated with adverse prognosis [ 30 , 128 , 129 , 130 ]. Recent studies have reported on the promoter methylation-dependent silencing of RASSF4 (RAS association domain family member 4), occurring with MM disease progression; with a correlation with adverse prognosis [ 131 ].…”
Section: Role Of Epigenetics In Supporting the Mgus-to-mm Transitimentioning
confidence: 99%
“…Genome-wide methylation arrays have been performed at several stages of MM disease, demonstrating the occurrence of DNA hypomethylation at early MM phases; importantly, the hypomethylated status was shown to further decline during MM progression [ 34 ]. Notably, promoter hypermethylation of several cancer-related genes (i.e., BNIP-3, p16, E-CAD, DAPK-1), was reported to correlated with adverse prognosis [ 30 , 128 , 129 , 130 ]. Recent studies have reported on the promoter methylation-dependent silencing of RASSF4 (RAS association domain family member 4), occurring with MM disease progression; with a correlation with adverse prognosis [ 131 ].…”
Section: Role Of Epigenetics In Supporting the Mgus-to-mm Transitimentioning
confidence: 99%
“…In addition, a high mutation rate in SOCS genes was observed in patients with ovarian cancer [16]. SOCS genes methylation may play important roles in carcinogenesis and tumor progression and may be used as diagnostic and prognostic tumor biomarkers [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, MGMT is tightly related to the prognosis of breast cancer, esophageal cancer, and glioma [39][40][41]; LCAT is veri ed to be markedly correlated with the prognosis of HCC, which has constituted a 4-gene signature with SPINK1, TXNRD1, and PZP [42]. Additionally, CISH is associated with the prognosis for patients with gallbladder carcinoma, breast cancer, prostate cancer, and multiple myeloma [43][44][45].…”
Section: Discussionmentioning
confidence: 99%